A process-based numerical approach to estimate forest groundwater consumption in flatland petrocalcic soils - Mujica, Claudio Ramón; Milione, Germán Marcelo; Bea, Sergio Andrés; Gyenge, Javier (International Water Association Publishing, 2020)
Grasslands are extensively distributed in flatland areas around the world such as the Pampas in South-America. It is one of the most economically productive landscapes and, as in other regions, they are being replaced by forests at increasing rates. Soil salinization emerges as a negative consequence associated with water deficit and forest groundwater consumption (~250-500 mm/yr, in this region). Assessment of forest groundwater consumption is crucial in risk evaluation of soil salinization on flatland environments. For this aim, numerical modeling based on physical/biological processes and atmospheric boundary conditions was successfully applied in monitored grassland and afforested plots. Modeling results suggested a partial hydraulic disconnection between forest and phreatic aquifer due to the presence of petrocalcic horizons. Forest transpiration estimates were approximately ~13% of total groundwater usage. Forest water consumption was then restricted to that soil portions of above the petrocalcic horizons. Estimated forest transpiration rates (~723 mm/yr) were similar to and even exceed those reported in salinized sites with similar features. However, the risk of salinization of these soils was unlikely, because forest transpiration was restricted to the upper soil portions filled with fresh rain water. The petrocalcic horizon retained water and prevented both deep drainage and indirectly, soil salinization.